2008
DOI: 10.1093/ndt/gfn210
|View full text |Cite
|
Sign up to set email alerts
|

Short daily haemodialysis: survival in 415 patients treated for 1006 patient-years

Abstract: Survival of patients on short daily haemodialysis was 2-3 times better than that of matched three times weekly haemodialysis patients reported by the USRDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 27 publications
4
152
1
5
Order By: Relevance
“…Published estimates of mortality risk reductions with daily hemodialysis range from 36% to 66% in as-treated analysis (Table 4). [7][8][9][10][11] All except one of these studies used the adjustment technique of indirect standardization to derive standardized mortality ratios, with the United States in-center population as the referent. Although this statistical approach is theoretically adequate, it is not well suited for high-dimensional adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published estimates of mortality risk reductions with daily hemodialysis range from 36% to 66% in as-treated analysis (Table 4). [7][8][9][10][11] All except one of these studies used the adjustment technique of indirect standardization to derive standardized mortality ratios, with the United States in-center population as the referent. Although this statistical approach is theoretically adequate, it is not well suited for high-dimensional adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Whether such mechanisms result in lower mortality risk is unknown, as observational studies that have reported improved survival with more frequent dialysis were relatively small and/or incompletely adjusted for selection bias. [7][8][9][10][11] The popularity of home hemodialysis has recently risen in the United States. According to the ESRD Network Organizations Program, the number of home hemodialysis patients increased from 1481 at the end of 2004 to 4836 at the end of 2009.…”
mentioning
confidence: 99%
“…This is a small number if compared with over 50 papers per year focused on dialysis start, and the growing attention on the importance of preserving renal function in dialysis patients, in large series and in sporadic case reports (41)(42)(43)(44)(45)(46)(47). Our review, which includes both large series and case reports, is in line with a brilliant previous review that focused on large series reporting on renal function recovery, and that suggests that this even may be encountered in the clinical practice in at least 1% of the patients who start dialysis with a chronic, life-long perspective of renal replacement therapy (Tabs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have reported that use of home HD improves survival for those patients on dialysis compared with those on in-center HD, [7][8][9][10][11][12] and approaches longevity offered by deceased donor transplantation. 5,6 Home HD has also been reported to offer improved wellbeing and enhanced patient lifestyle.…”
Section: The Global Forum For Home Hemodialysis Initiativementioning
confidence: 99%